2018
DOI: 10.1002/2017jb014566
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Attenuation and Stiffness Modulus Dispersion in Porous Rocks Containing Stochastic Fracture Networks

Abstract: Understanding seismic attenuation and modulus dispersion mechanisms in fractured rocks can result in significant advances for the indirect characterization of such environments. In this paper, we study attenuation and modulus dispersion of seismic waves caused by fluid pressure diffusion (FPD) in stochastic 2‐D fracture networks, allowing for a state‐of‐the‐art representation of natural fracture networks by a power law length distribution. To this end, we apply numerical upscaling experiments consisting of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 37 publications
2
39
0
2
Order By: Relevance
“…These observations are consistent with those of Guo, Rubino, Barbosa, et al, (), Guo, Rubino, Barbosa, et al, (), and Guo, Rubino, Glubokovskikh, et al, (), which found that the 3‐D (penny‐shaped cracks) theoretical predictions are in good agreement with the 2‐D (slit cracks) numerical simulations after scaling the elastic moduli in the low‐ and high‐frequency limits. Similar conclusions are also drawn by Barbosa et al () and Hunziker et al () through the comparison of the 2‐D and 3‐D numerical simulations for the aligned fracture cases. The comparison of the theoretical models for the slit and penny‐shaped cracks in this paper confirms that the seismic dispersion and attenuation due to WIFF for waves perpendicular to fractures are relatively insensitive to the largest dimension (“length”) of the fractures.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These observations are consistent with those of Guo, Rubino, Barbosa, et al, (), Guo, Rubino, Barbosa, et al, (), and Guo, Rubino, Glubokovskikh, et al, (), which found that the 3‐D (penny‐shaped cracks) theoretical predictions are in good agreement with the 2‐D (slit cracks) numerical simulations after scaling the elastic moduli in the low‐ and high‐frequency limits. Similar conclusions are also drawn by Barbosa et al () and Hunziker et al () through the comparison of the 2‐D and 3‐D numerical simulations for the aligned fracture cases. The comparison of the theoretical models for the slit and penny‐shaped cracks in this paper confirms that the seismic dispersion and attenuation due to WIFF for waves perpendicular to fractures are relatively insensitive to the largest dimension (“length”) of the fractures.…”
Section: Discussionsupporting
confidence: 87%
“…Guo et al (2017), Guo, Rubino, Barbosa, et al, (2018a), Guo, Rubino, Barbosa, et al, (2018b), and Guo, Rubino, Glubokovskikh, et al, (2018) compared the results of numerical simulations for slit fractures (2-D numerical simulation) against the theoretical model designed for the penny-shaped fractures ; a 3-D theoretical result) and found a surprisingly good agreement, despite the difference in underlying geometries. This phenomenon was further explored in recent numerical simulations of Hunziker et al (2018), which show that attenuation and dispersion caused by 3-D cracks is very close to that caused by 2-D cracks. Although there is no clear theoretical explanation as yet for this agreement, it implies that the seismic dispersion and attenuation due to WIFF is relatively insensitive to the largest dimension ("length") of the fractures.…”
mentioning
confidence: 91%
“…Additionally, the larger crack volume makes the 2.5D model more compressible as evidenced by a generally lower real-valued P-wave modulus, which also contributes to the increase in attenuation. The comparison between numerical results from a 3D cubic model with those of a 2D model points to the importance of 3D effects that are neglected in studies based on 2D models, as shown by Hunziker et al (2018). An important aspect is that 2D models overestimate attenuation.…”
Section: O M P a R I S O N W I T H A N A L Y T I C A L S O L U T I O Nmentioning
confidence: 84%
“…The comparison between numerical results from a 3D cubic model with those of a 2D model points to the importance of 3D effects that are neglected in studies based on 2D models, as shown by Hunziker et al . (). An important aspect is that 2D models overestimate attenuation.…”
Section: Comparison With Analytical Solutionmentioning
confidence: 99%
“…In a poroelastic framework, pressure diffusion phenomena, such as wave-induced fluid flow and squirt flow, have been studied numerically (e.g. Rubino et al 2013Rubino et al , 2014Rubino et al , 2017Quintal et al 2014;Vinci, Renner and Steeb 2014;Hunziker et al 2018) and analytically (e.g. Chapman 2003;Gurevich et al 2009;Guo et al 2016), whereas scattering in fractured media is commonly studied in an elastic context (e.g.…”
mentioning
confidence: 99%